Analysis of the credit and investment activities of the Ukrainian banks - Olga Zaslavska (Cхід, 2013)
The article reviews the theoretical and practical aspects of credit and investment activity of domestic banks. There was estimated the credit and investment portfolio of the banking sector of Ukraine. Due to the current state of economy there were considered trends in credit and investment banking.